1996
DOI: 10.1097/00042560-199610010-00009
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis and HIV Infection Among Female Inmates in São Paulo, Brazil: A Prospective Cohort Study

Abstract: Prison populations are at increased risk of both human immunodeficiency virus (HIV) and Mycobacterium tuberculosis infections, but among female inmates information on such risks remains scarce, especially in developing countries. Between October 1992 and November 1993, 350 women incarcerated at a prison in São Paulo, Brazil, were prospectively evaluated for HIV and M. tuberculosis infection and disease. Among them, 87 (25%) were HIV seropositive, and 20 (5.7%) had tuberculosis (TB). During the incarceration pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 13 publications
1
33
0
5
Order By: Relevance
“…Our results also demonstrate that most of the isolates may be allocated to two main clusters. This denotes that just a few strains may be responsible for the colonization of the hosts and prevail due to the close proximity between inmates, as corroborated by Ferreira et al [24], who studied 350 female inmates and found only seven RFLP patterns for the studied M. tuberculosis strains.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Our results also demonstrate that most of the isolates may be allocated to two main clusters. This denotes that just a few strains may be responsible for the colonization of the hosts and prevail due to the close proximity between inmates, as corroborated by Ferreira et al [24], who studied 350 female inmates and found only seven RFLP patterns for the studied M. tuberculosis strains.…”
Section: Discussionsupporting
confidence: 60%
“…In the last years, considerable efforts have been made to precise the epidemiology and characteristics of M. tuberculosis strains isolated in different regions of Brazil [7,[24][25][26][27][28][29][30][31]. Some Brazilian authors [26,27,29,32] demonstrated the usefulness of the IS6110-restriction fragment length polymorphism for typing Brazilian M. tuberculosis strains, but Ferreira et al [24] were the first to apply it to determine strain types in female inmate populations in São Paulo City, Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Biópsia cervical (N=15*) Cervicite crônica 5 33,3 Hiperplasia epitelial escamosa (acantose) sem discariose significativa 6 40,0 NIC*** i + HPV*** 3 20,0 NIC** ii + HPV*** 1 6 , 7 *Três mulheres não participaram desta fase de exames **Mulheres que apresentaram alterações colposcópicas e necessitaram de biópsia ***NIC: neoplasia intra-epitelial cervical ****HPV: papilomavírus humano rência de comportamentos de risco para DST entre presidiárias do que na população geral. 5,9,11 As características sociodemográficas das participantes refletem as apresentadas pela maioria das mulheres de baixa renda do Estado do Espírito Santo: mulheres pardas, casadas ou amasiadas, na faixa etária média de 30 anos, com pouca escolaridade e trabalho sem qualificação. * No entanto, a amostra estudada no presente estudo não é representativa dessa população, pois difere em relação a outros aspectos analisados, como o uso de drogas e a criminalidade.…”
Section: Discussionunclassified
“…Há poucos trabalhos publicados que investigaram os problemas de saúde da mulher em prisões brasileiras, mais especificamente as doenças infecciosas e DST. 5 Confinada e acessível, a população encarcerada deveria receber uma abordagem orientada para a detecção e tratamento de doenças e identificação de fatores de risco, fundamentada por ações de educação e aconselhamento. Para orientar e viabilizar a implantação de tais medidas, o presente estudo teve por finalidade identificar os problemas de saúde e o perfil sociodemográfico da população feminina encarcerada, provendo, sempre que necessário, orientação e tratamento clínico às detentas.…”
Section: Introductionunclassified